EXPLORING THE POTENTIAL OF QUANTUM COMPUTING IN REVOLUTIONISING RISK MANAGEMENT AND DIGITAL FINANCIAL SECURITY - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2025)
Quantum computing offers revolutionary potential in the transformation of risk management and digital financial security. With the ability to process large-scale and complex data exponentially faster than classical computers, this technology enables risk analysis, portfolio optimisation and fraud detection to be performed with much greater accuracy and efficiency. Quantum algorithms such as the Quantum Approximate Optimisation Algorithm (QAOA) and quantum-based Monte Carlo simulations have been shown to improve the speed and precision of risk prediction in the financial sector, while innovations such as Post-Quantum Cryptography (PQC) and Quantum Key Distribution (QKD) are becoming key solutions to address the security threat of quantum computers' ability to break conventional encryption. However, the adoption of these technologies still faces major challenges, such as hardware limitations, high implementation costs, the need for skilled personnel, and the need for standardisation of new security algorithms. With continued research investment and cross-sector collaboration, quantum computing has the potential to shape a more resilient, adaptive and secure digital financial ecosystem in the post-quantum era.